2023
DOI: 10.1186/s12957-023-03236-x
|View full text |Cite
|
Sign up to set email alerts
|

Implication of perineural invasion in patients with stage II gastric cancer

Dandong Luo,
Yue-e Wen,
Huaxian Chen
et al.

Abstract: Background Perineural invasion (PNI) is regarded as a prognostic factor for patients with GC. However, the significance of PNI in patients with stage II GC remains unclear. This study aimed to investigate the clinical implication of PNI in patients with stage II GC undergoing curative resection. Methods Patients with stage II GC who underwent curative resection were retrospectively evaluated from January 2010 to July 2019. According to PNI status, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Recent findings suggested that patients with PNI who undergone adjuvant chemotherapy experience improved postoperative OS and DFS ( 40 ). Hence, the nomogram model presented here not only effectively predicted preoperative PNI status but also contributed to postoperative risk stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings suggested that patients with PNI who undergone adjuvant chemotherapy experience improved postoperative OS and DFS ( 40 ). Hence, the nomogram model presented here not only effectively predicted preoperative PNI status but also contributed to postoperative risk stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings suggested that patients with PNI who undergone adjuvant chemotherapy experience improved postoperative OS and DFS (40). Hence, the nomogram model presented here not only effectively predicted preoperative PNI status but also contributed to postoperative risk stratification.…”
Section: Discussionmentioning
confidence: 76%